Evaluasi Perbandingan Penjualan Offline dan Online Terhadap Pendapatan (Studi Kasus pada Kedai Cak Mat Ali Kota Bangkalan) - Ach Arif; Octaviana Arisinta; Romiftahul Ulum (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
In this increasingly developing era, it requires entrepreneurs to be able to continue to develop their business because of increasingly fierce competition, entrepreneurs must have a sales strategy so that the business they are running can continue to survive and can grow and be recognized by the wider community. Kedaia Cak Mata Ali is a business engaged in the food and beverage sector. research was conducted to determine the comparison of offline and online sales of income. The type of data analysis used in this research is descriptive qualitative. Data collection techniques are observation, interviews. And documentation. Analysis of data from research can obtain results of a comparison of offline and online sales to income. It can be seen that offline sales have greater income than online sales. because consumers prefer to buy directly at the cak mata ali shop because prices are cheaper compared to buying online and consumers are more satisfied when buying directly at the shop because the goods purchased can be according to performance.